La mémoire de la Grande Guerre à travers les odonymes en France - Clément Millon (EchoGéo)
The living memory of the past can be measured by the management of odonyms (route and place names). The presence of the Great War in France by studying of the actual FANTOIR file is significant. But the number of odonyms who commemorates the second world war, or other conflicts, is more important. We have to ask what the cause of that is.